Attitudinal meaning in the syllabus of same-sex marriage legal document of the United States: a systemic functional linguistics approach - Ulfah, Ayu Pratiwi; Sujatna, Eva Tuckyta Sari; Amalia, Rosaria Mita (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2019)
After being recognized as a legitimate form of marriage in various countries, the Supreme Court of the United States ruled that the American Constitution guarantee the marriage of same-sex. Â It is the syllabus of same-sex Marriage in the United States that become the object of the research. This thesis aims to identify the attitude types and clauses constituent of syllabus constructed by same-sex marriage proposer in the United States and examines how attitude types inÂ the syllabus of Same-sex Marriage in the United States indicates the meaning and relation with the readers. The theory proposed by Martin and White of Appraisal system (2005) based on attitude types is used to support the analysis. The research found that the attitude types in same-sex marriage syllabus there are 92 affect, 54 judgement, and 58 appreciation. Based on the attitudinal types in this research, the same-sex proposers feeling indicates they are being discriminated because their citizenship rights have not been fulfilled. It can be seen from the most choice of the word "harm" that indicates the existence of a condition that there is a rule injustice. Therefore the same-sex proposers need to be protected their right to marry the same-sex couples. Validation the right of same-sex marriage, will give them a guarantee to live safely. If the right cannot be avowed, the same-sex actor will be suspected as a criminal by the state. The same-sex proposers believe this is harmful decision. Because they think that marriage is an important right that everyone can procure it, including the same-sex orientation. This right cannot be parting from the other right and same-sex marriage right must be legalized by the state. Therefore the state must to treat the citizen equally.